Gender Comparison Of Economic Status Of The Elderly In Peninsular Malaysia - Gikonyo, Lucy W. (2007)

(untitled)
The purpose of this study was to investigate the economic status of elderly men and women in Peninsular Malaysia using their net flow (income less expenditures) and net worth (assets less liabilities). The study utilized secondary data from an IRPA Project titled “Economic and Financial Aspects of Ageing in Malaysia (2005)” the research programme on Quality of Life of Older Malaysians. The dataset contained information on 1841 elderly (926 females and 915 males) aged 55-75 from Peninsular Malaysia. The dataset contained a range of information on the elderly including their demographics. This study analyzed and described selected portions of the dataset which had variables that corresponded to the objectives of the study.Twelve variables were selected and used in this research. Their basis for inclusion was the literature reviewed for this study. These variables included age, sex, ethnicity, marital status, educational attainment, employment status, home ownership, perceived health status, assets, liabilities, income and expenditure. The data was at the individual level except for expenditure data which was at the household level. Analysis was run using SPSS version 13. Tests run were ANOVA, T-tests and Discriminant analysis.The results of the study revealed that elderly males and females differ in their economic status. For instance, when both net flow and net worth are taken into consideration, 79% males compared to 72% females have positive net flow. The data further revealed that 89% males compared to 71% females had positive net worth. Elderly men reported earning an income from multiple sources compared to women who predominantly reported social income (money from children) as their main source of income. Income did not tell the whole story about the elderly’s economic status because the elderly have had the opportunity to accumulate assets throughout their life cycle and can draw on these assets to support their consumption as they advance in age The study further assessed the economic status of the elderly using a combined net worth and net flow measure resulting into four typologies. The respondents values of net worth and net flow were used to profile them into four typologies: i) those with positive net flow and positive net worth ii) those with positive net flow and negative net worth iii) those with negative net flow and positive net worth iv) those with both negative net flow and negative net worth. Only 40% of the respondents were correctly grouped as revealed by discriminant analysis results. This means that the model needs further improvement.The typologies revealed that 70% of elderly males and 53% elderly females had both positive net flow and net worth. Those with both negatives comprised 3% males and 10% females. This research implies that elderly men and women differ in their resources and consequently economic status. Different measures should be taken as indicators of economic status of both elderly men and women.